Shear-thinning effects of hemodynamics in patient-specific cerebral aneurysms - Alberto Gambaruto; João Janela; Alexandra Moura; Adélia Sequeira (Mathematical Biosciences and Engineering)
Two different generalized Newtonian mathematical models for blood flow, derived for the same experimental data, are compared, together with the Newtonian model, in three different anatomically realistic geometries of saccular cerebral aneurysms obtained from rotational CTA. The geometries differ in size of the aneurysm and the existence or not of side branches within the aneurysm.Results show that the differences between the two generalized Newtonian mathematical models are smaller than the differences between these and the Newtonian solution, in both steady and unsteady simulations.